Coming to stay or to go? Stay intention and involved uncertainty of international students - Fabian Koenings; Tina Haußen; Stefan Töpfer; Silke Übelmesser (Friedrich Schiller University Jena, 2019)
Countries compete for young talents to alleviate skilled-labor shortage. International students, who stay after graduation, allow host countries to overcome those challenges. This study investigates the factors associated with international students' intention to stay or to go after graduation. In contrast to the existing literature, this analysis employs survey data collected at the beginning of the studies. This assures that the analysis is not distorted by attrition and provides policymakers with more time for interventions. At the same time, it requires to deal with uncertainty as the actual migration decision will only be due in a few years. This study introduces a set of uncertainty models to the migration context to account for this. It finds that the results are largely robust across the different models: lower economic growth in the home country, a stay in the host country before the studies and being enrolled in a Bachelor program instead of a Master program are significantly associated with the intention to stay with certainty. Furthermore, Master students are found to be more uncertain than Bachelor students.
Keywords: F22; J24; I23; 330; Stay intention; International students; Uncertainty; Labor shortage